Introduction to Epidemiology and Control of Peste des Petits Ruminants (Eco-PPR) tools. 5.2 Market Survey―Research Guide - Wieland, Barbara; Dione, Michel M.; Okoth, Edward A.; Jones, B.; Kotchofa, Pacem; Campbell, Zoë A.; Rutto, Erick (International Livestock Research Institute, 2020)
This tool collects information about the buying and selling of small ruminants in markets in order to understand market networks and potential spread of disease.